Manganese(II) catalyzes the bicarbonate-dependent oxidation of amino acids by hydrogen peroxide and the amino acid-facilitated dismutation of hydrogen peroxide. - Berlett, B S (1990)
In bicarbonate/CO2 buffer, Mn(II) and Fe(II) catalyze the oxidation of amino acids by H2O2 and the dismutation of H2O2. As the Mn(II)/Fe(II) ratio is increased, the yield of carbonyl compounds per mole of leucine oxidized is essentially constant, but the ratio of alpha-ketoisocaproate to isovaleraldehyde formed increases, and the fraction of H2O2 converted to O2 increases. In the absence of Fe(II), the rate of Mn(II)-catalyzed leucine oxidation is directly proportional to the H2O2, Mn(II), and amino acid concentrations and is proportional to the square of the HCO3- concentration. The rate of Mn(II)-catalyzed O2 production in the presence of 50 mM alanine or leucine is about 4-fold the rate observed in the absence of amino acids and accounts for about half of the H2O2 consumed; the other half of the H2O2 is consumed in the oxidation of the amino acids. In contrast, O2 production is increased nearly 18-fold by the presence of alpha-methylalanine and accounts for about 90% of the H2O2 consumed. The data are consistent with the view that H2O2 decomposition is an inner sphere (cage-like) process catalyzed by a Mn coordination complex of the composition Mn(II), amino acid, (HCO3-)2. Oxidation of the amino acid in this complex most likely proceeds by a free radical mechanism involving hydrogen abstraction from the alpha-carbon as a critical step. The results demonstrate that at physiological concentrations of HCO3- and CO2, Mn(II) is able to facilitate Fenton-type reactions.